1992
DOI: 10.1152/ajpregu.1992.262.3.r407
|View full text |Cite
|
Sign up to set email alerts
|

Preoptic norepinephrine-induced hypothermia is mediated by alpha 2-adrenoceptors

Abstract: We have shown previously that norepinephrine (NE) microdialyzed into the preoptic area of conscious guinea pigs evokes a fall in core temperature (Tco) that is mediated by a reduction in metabolic rate. To identify the adrenoceptor subtype(s) involved in this effect, we microdialyzed intrapreoptically various adrenergic agonists or antagonists singly or in combinations. Tco and ear skin temperatures of the animals were monitored throughout the experiments. alpha 1-, beta-, beta 1-, and beta 2-agonists and anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 0 publications
5
40
0
1
Order By: Relevance
“…Since norepinephrine also acts at alpha-2 ARs to produce an initial hypothermic effect (Quan et al, 1992), it may be presumed that their activation results in responses for these two populations of POAH neurons that contrast those we have shown for the alpha-1 AR agonist Cirazoline, but this remains to be tested. This early hyperthermia likely attenuates due to eventual desensitization at the postsynaptic alpha-1 ARs, the induction of COX-2 expression by activation of alpha-2 ARs, ensuing PGE 2 synthesis, and action at Prostaglandin E receptors (EP; presumably the EP 3 subtype) which contribute the late phase of fever (Feleder et al, 2007;Lazarus et al, 2007;Oka, 2004).…”
Section: Discussionmentioning
confidence: 73%
“…Since norepinephrine also acts at alpha-2 ARs to produce an initial hypothermic effect (Quan et al, 1992), it may be presumed that their activation results in responses for these two populations of POAH neurons that contrast those we have shown for the alpha-1 AR agonist Cirazoline, but this remains to be tested. This early hyperthermia likely attenuates due to eventual desensitization at the postsynaptic alpha-1 ARs, the induction of COX-2 expression by activation of alpha-2 ARs, ensuing PGE 2 synthesis, and action at Prostaglandin E receptors (EP; presumably the EP 3 subtype) which contribute the late phase of fever (Feleder et al, 2007;Lazarus et al, 2007;Oka, 2004).…”
Section: Discussionmentioning
confidence: 73%
“…Noradrenaline administered in the preoptic area induces a hypothermic response because of a reduction in the metabolic rate (Quan et al, 1991). This response has been shown to be mediated by -2 receptors, as demonstrated by the fact that an -2 agonist evoked a dose-dependent decrease in body temperature that was abolished by an -2 antagonist (Quan et al, 1992). Similar results were found after noradrenaline activation in the anterior hypothalamus during rest and exercise (Feleder et al, 2004;Gisolfi & Christman, 1980).…”
Section: Noradrenalinementioning
confidence: 52%
“…The literature points out that the divergent thermal effects of noradrenaline depend on the t y p e o f r e c e p t o r t h a t i s b e i n g s t imulated. Therefore, it seems that -1 noradrenergic receptors mediate a rise in body temperature, while -2 noradrenergic receptors are involved in a fall in body temperature (Feleder et al, 2004;Imbery et al, 2008;Quan et al, 1991Quan et al, , 1992. Noradrenaline administered in the preoptic area induces a hypothermic response because of a reduction in the metabolic rate (Quan et al, 1991).…”
Section: Noradrenalinementioning
confidence: 99%
“…Administration of noradrenaline or clonidine to the preoptic area of the guinea-pig hypothalamus elicits hypothermia that is blocked by coadministration of yohimbine or rauwolscine (Quan et al, 1992). Earlier studies have shown that the hypothermia caused by low dose clonidine (0.05 mg kg-', i.p.)…”
Section: Discussionmentioning
confidence: 99%
“…The lack of inhibitory effect of naloxone indicated that the hypothermia elicited by clonidine does not depend on opioid-mediated mechanisms. The lack of sensitivity to an a2-induced hypothermia in STZ-treated rats could also be due to abnormality at central or peripheral sites, since the hypothalamic control is exercised through reduction in metabolic heat production (Quan et al, 1992). The similarity of the response to the peripheral vasodilator nicotinic acid would appear to exclude gross vascular changes in diabetes as causes of the inversion of the thermoregulatory response to clonidine.…”
Section: Discussionmentioning
confidence: 99%